2021
DOI: 10.1097/bpo.0000000000001974
|View full text |Cite
|
Sign up to set email alerts
|

Tiered Guidelines in a Pediatric Orthopaedic Practice Reduce Opioids Prescribed at Discharge

Abstract: Background: Data regarding opioid prescribing patterns following pediatric orthopaedic procedures is limited. The aim of this work was to evaluate the effects of tiered guidelines for discharge opioid prescriptions following common pediatric orthopaedic procedures. Methods: Quality improvement project conducted at a single academic institution. Guidelines for discharge opioid prescriptions were implemented January 2018 and established 4 tiers of increasing invasiveness for 28 common pediatric orthopaedic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One single-institution pediatric opioid prescribing guideline implemented by Jones et al 20 for orthopaedic patients achieved a 54% reduction in prescribed opioids. Likewise, Baker et al 28 demonstrated decreased opioid prescribing variability associated with a 4-tier discharge opioid prescribing guideline. We recommend orthopaedic surgeons utilize evidence-based data such as these, or the results of their own experience monitoring medication consumption to achieve similar reductions in opioid prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…One single-institution pediatric opioid prescribing guideline implemented by Jones et al 20 for orthopaedic patients achieved a 54% reduction in prescribed opioids. Likewise, Baker et al 28 demonstrated decreased opioid prescribing variability associated with a 4-tier discharge opioid prescribing guideline. We recommend orthopaedic surgeons utilize evidence-based data such as these, or the results of their own experience monitoring medication consumption to achieve similar reductions in opioid prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…In another randomized trial, Vincent et al highlighted again that patient education reduced the number and duration of pills taken, but there is still a grave overprescription of opioids, as they reported that approximately 50% of prescribed pills went unused 75 . Additional methods to reduce pills in circulation may be handouts on proper pill disposal 76 , tiered prescribing guidelines based on procedure type 77,78 , and prescriptions written in 3 equal distributions 79 .…”
Section: Practice Managementmentioning
confidence: 99%
“…4 Many institutions are taking steps to optimize analgesia regimens to limit opioid prescriptions for an array of procedures. 5,6 Other groups have focused on demonstrating the efficacy of non-opioid pain medication, with three randomized control trials showing non-opioid pain medication to be as effective as opioids when treating extremity injury pain in children. [7][8][9] Non-opioid pain management following closed reduction and percutaneous pinning (CRPP) for Gartland Type II and III supracondylar humerus (SCH) fractures has become an area of focus within pediatric orthopaedics.…”
Section: Introductionmentioning
confidence: 99%